Gas leakage monitoring system using raspberry Pi 3 model B and IoT solution for smart home / Mohd Ierokie Pauzi - Pauzi, Mohd Ierokie (2018)
This paper presents the safety and preventing system for home, which is gas leakage monitoring system using Raspberry Pi 3 and internet of things (IoT) solution. The main function of this system is to detect the existing leakage gas and the consumer through the wireless system by the notification to their smartphone. For preventing measure, this system will automatically turn off the gas valve at the gas tank. This system will continuously monitor the existing of the liquefied petroleum gas (LPG) if the power supply is not turn off. This system provides and ensure safety for consumer and prevents from the explosion to leakage gas. This system ISA implemented by using the latest and newest microcontroller that is Raspberry Pi 3 model B.